The Relationship between Customer Value with eWOM and Customer Satisfaction as an Intervening Variable for Generation Y and Generation Z Boba Drink Consumers - Betarisha Putri; Zulfikar Fauzi (Journal of Applied Digital Business Management, 2024)
Boba drinks have become a contemporary beverage trend gaining popularity, particularly among Generation Y and Generation Z. These two generations coexist with technological advancements such as the internet. However, in this rapidly evolving industry, competition is becoming increasingly fierce, as reflected in the rising number of boba beverage outlets in Indonesia. This research aims to explore the relationship between Customer Value, Electronic Word of Mouth, and Customer Satisfaction as Intervening Variables among Generation Y and Generation Z Boba Drink Consumers. Customer Value encompasses four dimensions: emotional value, social value, quality value, and cost value. Customer satisfaction is measured through the dimensions of product and service attributes. Electronic Word of Mouth is assessed using three dimensions: intensity, content, and opinion valence. The research employs descriptive and verification methods, targeting consumers of boba drinks from Generation Y and Generation Z. Questionnaires were distributed to 165 respondents from each generation. Data were analyzed using path analysis. Hypotheses were tested using t-tests and Mann-Whitney tests to determine differences. The results indicate a strong relationship between customer value and customer satisfaction and a relationship between customer satisfaction and electronic word of mouth. Additionally, differences in boba drink consumer behavior between Generation Y and Generation Z were identified